Intubation first-pass success in a high performing pre-hospital critical care system is not associated with 30-day mortality: a registry study of 4496 intubation attempts - Ljungqvist Harry; Pirneskoski Jussi; Saviluoto Anssi; Setälä Piritta; Tommila Miretta; Nurmi Jussi (BMC, 2023)
Background
Lower intubation first-pass success (FPS) rate is associated with physiological deterioration, and FPS is widely used as a quality indicator of the airway management of a critically ill patient. However, data on FPS's association with survival is limited. We aimed to investigate if the FPS rate is associated with 30-day mortality or physiological complications in a pre-hospital setting. Furthermore, we wanted to describe the FPS rate in Finnish helicopter emergency medical services.
Methods
This was a retrospective observational study. Data on drug-facilitated intubation attempts by helicopter emergency medical services were gathered from a national database and analysed. Multivariate logistic regression, including known prognostic factors, was performed to assess the association between FPS and 30-day mortality, collected from population registry data.
Results
Of 4496 intubation attempts, 4082 (91%) succeeded on the first attempt. The mortality rates in FPS and non-FPS patients were 34% and 38% (P = 0.21), respectively. The adjusted odds ratio of FPS for 30-day mortality was 0.88 (95% CI 0.66-1.16). Hypoxia after intubation and at the time of handover was more frequent in the non-FPS group (12% vs. 5%, P < 0.001, and 5% vs. 3%, P = 0.01, respectively), but no significant differences were observed regarding other complications.
Conclusion
FPS is not associated with 30-day mortality in pre-hospital critical care delivered by advanced providers. It should therefore be seen more as a process quality indicator instead of a risk factor of poor outcome, at least considering the current limitations of the parameter.